The Influence of Organizational Culture and Organizational Commitment on the Performance of Maintenance Employees at PT Adis Dimension Footwear, Tangerang Regency - Rahman, Dendi Aulia; Cahyono, Yoyok (IJOSPOL - International Journal of Social, Policy and Law, 2026)
The purpose of this study was to determine how much influence organizational culture and organizational commitment have on the performance of employees in the Maintenance division at PT Adis Dimension Footwear, Tangerang Regency.This study uses a quantitative descriptive method. The population in this study were all employees in the Maintenance division at PT Adis Dimension Footwear, Tangerang Regency. The research sample consisted of 48 respondents.The results of this study indicate that (1) partially, organizational culture significantly influences the performance of employees in the Maintenance department at PT Adis Dimension Footwear, Tangerang Regency, as indicated by the calculated t value > t table (7.705 > 2.014) and a significance value of 0.000 which is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, organizational commitment significantly influences the performance of employees in the Maintenance department at PT Adis Dimension Footwear, Tangerang Regency, as indicated by the calculated t value > t table (3.865 > 2.014) and a significance value of 0.000 which is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, organizational culture and organizational commitment significantly influence the performance of employees in the Maintenance department at PT Adis Dimension Footwear, Tangerang Regency, as indicated by the calculated F value > F table (92.628 > 3.20) with a significance level of 0.000, thus Ha is accepted and H0 is rejected. Based on the results of the study, it can be concluded that the variables of organizational culture and organizational commitment, either partially or simultaneously, have a significant influence on the performance of employees in the Maintenance section at PT Adis Dimension Footwear, Tangerang Regency.